2001
DOI: 10.1113/eph8602178
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Current Research in Parturition

Abstract: The mechanism of human parturition is not understood and further research into this important physiological process is needed. Preterm labour remains a major cause of perinatal mortality and morbidity and there is controversy about the effectiveness of current tocolytic agents. In some species, notably the sheep, parturition is preceded by an activation of the fetal hypothalamic‐pituitary‐adrenal axis. However, in primates this axis has a supportive, rather than essential, role. A fall in maternal progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 55 publications
1
36
0
1
Order By: Relevance
“…The mechanism by which the myometrium is prepared for labor is not completely understood. However, it appears that cytokines such as TNF-␣ are involved in this mechanism (2,3,18,21,23,24). We (1) have previously shown that incubation of myometrial cells with TNF-␣ for Ͼ12 h increases expression of CD38, elevates intracellular levels of cADPR, and augments oxytocin-induced Ca 2ϩ transients.…”
Section: Role Of Cd38 On Myometrial Camentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which the myometrium is prepared for labor is not completely understood. However, it appears that cytokines such as TNF-␣ are involved in this mechanism (2,3,18,21,23,24). We (1) have previously shown that incubation of myometrial cells with TNF-␣ for Ͼ12 h increases expression of CD38, elevates intracellular levels of cADPR, and augments oxytocin-induced Ca 2ϩ transients.…”
Section: Role Of Cd38 On Myometrial Camentioning
confidence: 99%
“…The mechanisms regulating the preparation of the myometrium for labor are not completely understood. It appears that placental steroids and proinflammatory cytokines play an important role in the preparation of the myometrium for contraction and labor (2,3,18,21,23,24). Thus it is important to understand the signaling pathways regulated by hormones and cytokines in myometrial cells.…”
mentioning
confidence: 99%
“…Its withdrawal at any stage of pregnancy initiates muscle contraction leading to labor (52). G protein-coupled receptor (GPCR) activation and reversible Ca 2ϩ -dependent phosphorylation of myosin light chain (MLC), catalyzed by myosin light chain kinase (MLCK), is a major determinant of smooth muscle contraction (7,34). The regulation of contractility is described by GO terms such as G protein-coupled signaling, cell communication, channel activity (voltage-gated cation channels), all of which were very significant in the analysis of the significantly modulated genes in P4/E2 and RU486-treated cells in this study.…”
Section: Discussionmentioning
confidence: 99%
“…έναρξη της διαδικασίας του τοκετού εξαρτάται κατά κύ ριο λόγο από τον άξονα υποθάλαμος-υπόφυση-επινεφρί-δια του εμβρύου (Bernal 2001). Σημαντικό ρόλο στη δια δικασία του τοκετού διαδραματίζει το μυομήτριο, λόγω της ικανότητας του να συσπάται υπό την επίδραση νευρι κών, χημικών και μηχανικών παραγόντων (Carbillon και συν.…”
unclassified